Case Study: Exploration of Numeracy Through a Metacognitive Knowledge Approach - Santoso, Hajar Ahmad; Juniati, Dwi; Khabibah, Siti (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2025)
This study explores students' numeracy literacy skills through a metacognitive approach with the Metacognitive Awareness Inventory (MAI) framework. Four female subjects were selected based on their highest scores on knowledge of cognition and regulation of cognition. Data were collected through problem-solving tests and in-depth interviews, analyzed based on six indicators of numeracy literacy: understanding the context of the problem, data interpretation, problem solving, reflection and reasoning, mathematical communication, and decision making. The results showed that regulation of cognition supported effective reflection and evaluation, as seen in Subject 3, who solved the problem in a structured and confident manner. In contrast, Subject 4 took longer and often hesitated even though her steps were correct. Subjects 1 and 2, with a focus on knowledge of cognition, excelled in choosing strategies but required additional reflection to ensure accuracy. This study emphasizes the importance of integrating numeracy literacy and metacognitive strategies in learning to improve students' critical and reflective abilities.